The exit decision in the European venture capital market - Félix, E.; Pires, C.; Gulamhussen, M. A. (Quantitative Finance, 2014)
This article analyses the exit decision in the European venture capital market, studying when to exit and how it interacts with the exit form. Using a competing risks model we study the impact on the exit decision of the characteristics of venture capital investors, of their investments and of contracting variables. Our results reveals that the hazard functions are non-monotonic for all exit forms and suggest that, in Europe, Initial Public Offering candidates take longer to be selected than trade sales. Moreover our results show that, in Europe, venture capitalists associated with financial institutions have quicker exits (stronger for trade sales), and highlight the importance of contracting variables on the exit decision. An unexpected result is that the presence on the board of directors leads to longer investment durations.